Understanding Sea‐Level Rise and Variability 2010
DOI: 10.1002/9781444323276.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Past and Future Changes in Extreme Sea Levels and Waves

Abstract: Coastal impacts of sea -level change can result from individual extreme sea -level and wave events, or long -term fl uctuations in mean sea level, or most likely from a combination of processes. An example of a combined impact is the damage caused by Hurricane Katrina at New Orleans, which resulted in unprecedented storm -surge levels and failure of coastal defenses. This was compounded by the rate of local mean sea -level rise relative to the land level of the Mississippi Delta of several times the global ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 187 publications
(184 reference statements)
2
45
0
2
Order By: Relevance
“…At many coasts around the world, extreme sea levels are essentially determined by tides; however, this effect is negligible in the Baltic Sea due to the semi-enclosed nature of the basin. Lowe et al (2010) Richter et al 2011) extreme sea levels in recent decades and concluded thatglobally-there is little evidence of change in extreme sea levels over an extended period, a behaviour which differs significantly from the change in GMSL. In their quasi-global investigation, Menendez and Woodworth (2010) showed that recent change in extreme sea levels is mostly due to the change in MSL (by a shift in the frequency distribution), while meteorological contributions vary on timescales of years and decades but mostly show no clear long-term trend.…”
Section: Extreme Sea Levelsmentioning
confidence: 99%
“…At many coasts around the world, extreme sea levels are essentially determined by tides; however, this effect is negligible in the Baltic Sea due to the semi-enclosed nature of the basin. Lowe et al (2010) Richter et al 2011) extreme sea levels in recent decades and concluded thatglobally-there is little evidence of change in extreme sea levels over an extended period, a behaviour which differs significantly from the change in GMSL. In their quasi-global investigation, Menendez and Woodworth (2010) showed that recent change in extreme sea levels is mostly due to the change in MSL (by a shift in the frequency distribution), while meteorological contributions vary on timescales of years and decades but mostly show no clear long-term trend.…”
Section: Extreme Sea Levelsmentioning
confidence: 99%
“…Future climate projections for European coasts, based on model ensembles, show SLR rates similar to global values (Lowe et al, 2010;Church et al, 2013). For low greenhouse gas (GHG) emission scenarios (SRES B2-A1B; RCP 2.6) mean SLR is likely to be in the range of 0.26-0.54 m above 1990 levels by 2080-2100.…”
Section: Climate and Human Change Factorsmentioning
confidence: 74%
“…Similar evolution trends apply to storm surges although in all cases due attention should be paid to the different behavior of mean trend and variance characterizing storms (Lowe et al, 2010). For instance, (Conte and Lionello, 2013) presented variations up to ±5% for both positive and negative surges in the Mediterranean Sea.…”
Section: Climate and Human Change Factorsmentioning
confidence: 77%
“…Lowe et al [42] note that the rate and unpredictable nature of tsunamis means that they are probably under-estimated in probabilistic estimates of future extreme sea-level. In practice atmospheric drivers of extreme sea level such as mid-latitude and tropical storms are more amenable to analysis and prediction.…”
Section: The Importance Of the Oceansmentioning
confidence: 99%